Digital Divide: Alarming Agenda of Marxism on the Digital Education Sector - Neil Beeto Jerrin; Bhuvaneswari G (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
As this world progresses towards a phase where digital modes of education are no longer considered optional, it has become mandatory and the only means of schooling due to the effects of the pandemic, Covid-19. The education sector is now entirely under the wing of digitalization to accomplish its objectives. Even though education can only be carried out through digital means, the ease of accessibility for digital modes for people from every socioeconomic sector cannot establish the concept of 'Digital Divide.' This term explains the breach between people who do not have the resources to utilize the digital realm. This breach between the people in the Digital Divide universe lurks the agendas of Marxism. The people who are privileged to access digital life are the ones who are from a well-established socioeconomic background/ sector, and the underprivileged ones are from a sector where the accessibility of the digital modes of life, even for education, are hectic because of their socioeconomic standards. Thereby, an image of how Marxist agendas is on the Digital Divide's shadows can be seen.